Democracy as Civil Religion: Reading Alexis De Tocqueville in India. (January 2016) - Chakrabarti, Anindita
The article explores Alexis de Tocqueville's explication of democracy as 'civil religion' or the new sacred of modern times. In Democracy in America, Tocqueville analyzed democracy as a political system as well as a moral value. The article begins with Tocqueville's analysis of the religious roots of American democracy. Dissociated from the affairs of the state through the principle of 'disestablishment', religion became secure in civil society, whereas the concept of democracy became inviolable and 'set apart' as sacred. He noted that the power of the majority acquires an inviolable character in democracy that had the potential to turn against the very principles that it upholds. In the Indian context, the debate around a uniform civil code (UCC) is one such issue that captures this predicament. Working out a roadmap for Indian pluralism signposted with a constitutional commitment to equality, liberty and fraternity has proved to be a task fraught with moral and political complexities, if not impasse. The article argues that Tocqueville's discovery of the role of religion in civil society, his mistrust of democratic majoritarianism and his emphasis on understanding the 'practice' of democracy have something to offer to the polarized UCC debate in India.